2010
DOI: 10.1111/j.1399-3046.2009.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of hematopoietic stem cell transplantation in Korean children with hemophagocytic lymphohistiocytosis

Abstract: Chemoimmunotherapy-based treatments have improved the survival of patients with HLH, but outcomes of the patients are still unsatisfactory. We report here the outcome of Korean children with HLH who underwent HSCT, which was analyzed from the data of a nation-wide HLH registry. Retrospective nation-wide data recruitment for the pediatric HLH patients diagnosed between 1996 and 2008 was carried out by the Histiocytosis Working Party of the Korean Society of Hematology. Nineteen patients who received HSCT among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
1
24
2
1
Order By: Relevance
“…This may reflect the effects of HLH itself or HLH chemotherapy and immunosuppression on the transplant process, including increased organ related toxicity and increased susceptibility to pathogens. In comparison to data reported on cohorts of patients undergoing transplant for HLH associated with other gene defects (eg, perforin and munc 13-4) [39][40][41] it appears that the outcome for HLH associated with XLP1 is worse and may relate to the multiple immune deficits associated with SAP deficiency. By contrast all XLP1 patients who had no HLH manifestations (n ϭ 27) survived the HSCT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the effects of HLH itself or HLH chemotherapy and immunosuppression on the transplant process, including increased organ related toxicity and increased susceptibility to pathogens. In comparison to data reported on cohorts of patients undergoing transplant for HLH associated with other gene defects (eg, perforin and munc 13-4) [39][40][41] it appears that the outcome for HLH associated with XLP1 is worse and may relate to the multiple immune deficits associated with SAP deficiency. By contrast all XLP1 patients who had no HLH manifestations (n ϭ 27) survived the HSCT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The causal genes of FHL account for the structure, function, and metabolism of cytotoxic granules, such as PRF1 (FHL2), UNC13D (FHL3), STX11 (FHL4), and STXBP2 (FHL5) [2]. A potential risk of developing HLH is also a part of the clinical expressions of X-linked lymphoproliferative disease (XLP1 and XLP2), Chediak-Higashi syndrome, and Griscelli syndrome [3].Recent advances in SCT procedures have improved the survival rate of patients with FHL who undergo SCT after myeloablative conditioning, which now range from 45 to 65% [4][5][6][7][8][9][10][11]. However, there remain critical problems with SCT for FHL; early death from treatment-related events often associated with venoocclusive disease, and neurological sequelae in survivors.…”
mentioning
confidence: 99%
“…A recent Japanese survey revealed a curative effect of alloSCT on sHLH in 7 out of 11 patients (64%) with refractory EBV-HLH (Ogha et al, 2010). Similarly, Yoon et al reported that alloSCT could be a curative treatment not only for FHL, but also for relapsed/refractory sHLH (Yoon et al, 2010). Anecdotal reports have also shown the efficacy of alloSCT in M-HLH therapy (Chang et al, 2009;Goi et al, 1999;Kelly et al, 2011;Machaczka et al, 2011b).…”
Section: Stem Cell Transplantationmentioning
confidence: 97%